Indigénisme et pragmatisme au Mexique : l’expérience éducative de Carapan par Moisés Sáenz Garza - Philippe Schaffhauser (Journal de la Société des Américanistes)
Indigenism and Pragmatism in Mexico : the educative experience of Carapan by Moisés Sáenz Garza. The objective of this article is to shed light on the use and diffusion of certain pragmatist theses concerning the methods of the philosopher John Dewey’s instrumentalism in relation to indigenous issues in the first half of the 20th century. In my view, speaking of « use » does not imply an exercise whose purpose consists in copying and reproducing Dewey’s thoughts on the topic of education and moving them from one place to another but, rather, an attempt by Mexicans to interpret this ideology and to put it in motion in a specific reality and terrain. In other words, speaking of « Mexican indigenist pragmatism » tends to reveal how the ideas of Dewey’s pragmatism, linked to the relationship between democracy and education, have been continuously recreated during Mexico’s indigenist experience. I focus this general hypothesis concretely on the account of the implementation of a pilot project that was carried out in the Purhépecha region called La Cañada de los Once Pueblos, in the state of Michoacán, Mexico, from June 1932 to January 1933. That experience, coordinated by the pedagogue Moisés Sáenz Garza (1888-1941) – author of the aforementioned – must be understood as one of the important periods in the conformation of the indigenist policy of Mexico’s revolutionary state.